Marketing Mix Analysis In Increasing Furniture MSMEs Sales Volume In Cirebon District - Diana Octa; Rifa Rohidatul Aisya; Ramlah Puji Astuti (Publikasi Indonesia, 2024)
This research aims to determine and analyze the marketing mix such as product, price, place and promotion on furniture sales volume in Cirebon Regency. This research was conducted with the hope of increasing sales volume for furniture MSMEs in Cirebon Regency. This research uses quantitative research. The data used in the research uses primary data collected by distributing questionnaires to 100 MSME owners in Cirebon Regency. The method used in the research is Random Sampling. Data were analyzed using Partial Least Squares Structural equation modeling (SEM-PLS) with the Smart-PLS 3.0 application. Research findings show that Product and Promotion have a negative impact on sales volume. Apart from that, the Price and Place variables have a positive effect on sales volume.